2007
DOI: 10.1242/dev.013136
|View full text |Cite
|
Sign up to set email alerts
|

Functional analyses of genetic pathways controlling petal specification in poppy

Abstract: MADS-box genes are crucial regulators of floral development, yet how their functions have evolved to control different aspects of floral patterning is unclear. To understand the extent to which MADS-box gene functions are conserved or have diversified in different angiosperm lineages, we have exploited the capability for functional analyses in a new model system, Papaver somniferum (opium poppy). P. somniferum is a member of the order Ranunculales, and so represents a clade that is evolutionarily distant from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
119
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(127 citation statements)
references
References 61 publications
8
119
0
Order By: Relevance
“…In Arabidopsis (Arabidopsis thaliana), mutation in AP3 or PI caused identical phenotypes of second whorl petal conversion into a sepal structure and third flower whorl stamen into a carpel structure (Bowman et al, 1989;Jack et al, 1992;Goto and Meyerowitz, 1994). Similar homeotic conversions for petal and stamen were observed in the mutants of the AP3 and PI orthologs from a number of core eudicots such as Antirrhinum majus, Petunia hybrida, Gerbera hybrida, Solanum lycopersicum, and Nicotiana benthamiana (Sommer et al, 1990;Trö bner et al, 1992;Angenent et al, 1993;van der Krol et al, 1993;Yu et al, 1999;Liu et al, 2004;Vandenbussche et al, 2004;de Martino et al, 2006), from basal eudicot species such as Papaver somniferum and Aquilegia vulgaris (Drea et al, 2007;Kramer et al, 2007), as well as from monocot species such as Zea mays and Oryza sativa (Ambrose et al, 2000;Nagasawa et al, 2003;Prasad and Vijayraghavan, 2003;Yadav et al, 2007;Yao et al, 2008). This indicated that the function of the B class genes AP3 and PI is highly conserved during evolution.…”
mentioning
confidence: 81%
“…In Arabidopsis (Arabidopsis thaliana), mutation in AP3 or PI caused identical phenotypes of second whorl petal conversion into a sepal structure and third flower whorl stamen into a carpel structure (Bowman et al, 1989;Jack et al, 1992;Goto and Meyerowitz, 1994). Similar homeotic conversions for petal and stamen were observed in the mutants of the AP3 and PI orthologs from a number of core eudicots such as Antirrhinum majus, Petunia hybrida, Gerbera hybrida, Solanum lycopersicum, and Nicotiana benthamiana (Sommer et al, 1990;Trö bner et al, 1992;Angenent et al, 1993;van der Krol et al, 1993;Yu et al, 1999;Liu et al, 2004;Vandenbussche et al, 2004;de Martino et al, 2006), from basal eudicot species such as Papaver somniferum and Aquilegia vulgaris (Drea et al, 2007;Kramer et al, 2007), as well as from monocot species such as Zea mays and Oryza sativa (Ambrose et al, 2000;Nagasawa et al, 2003;Prasad and Vijayraghavan, 2003;Yadav et al, 2007;Yao et al, 2008). This indicated that the function of the B class genes AP3 and PI is highly conserved during evolution.…”
mentioning
confidence: 81%
“…However, silencing of PI in columbine, also a member of the Ranunculales and with multiple stamen whorls, results in organs with carpeloid identity in the position of the stamens and no sepal-like organs were observed (Kramer et al, 2007). Similarly, downregulation of either of the B genes in opium poppy did not result in sepal-like organs in whorls of wild-type stamens (Drea et al, 2007). Two scenarios are plausible to explain the evolution of this regulation of class C genes considering that recent comparative morphology analyses suggest that the ancestral angiosperm flower had more than two stamen whorls (or stamen series in species with spiral phyllotaxy) (Endress and Doyle, 2009).…”
Section: Class Gene Regulation By B Class Genesmentioning
confidence: 95%
“…The obligate B protein heterodimers in snapdragon and Arabidopsis are required both for organ identity specification and to maintain B gene expression in an autoregulatory circuit Tröbner et al, 1992;Zachgo et al, 1995;Davies et al, 1996;Hill et al, 1998;Tilly et al, 1998;Manchado-Rojo et al, 2012). In addition to heterodimers of AP3/PI-like proteins, homodimers of AP3 orthologs have been found in basal eudicots like columbine (Aquilegia vulgaris) and opium poppy (Papaver somniferum) (Drea et al, 2007;Kramer et al, 2007), whereas homodimer formation of PI orthologs has been demonstrated so far for petaloid monocots like the tulip (Tulipa gesneriana) and the orchid Phalaenopsis equestris (Kanno et al, 2003;Tsai et al, 2008). However, a function could not be assigned to homodimers formed by either AP3 or PI orthologs.…”
Section: Introductionmentioning
confidence: 99%
“…The finding that these proteins have the ability to homodimerize in some flowering plant species and in gymnosperms led to the hypothesis that obligate heterodimerization of DEF-and GLO-like proteins arose from homodimerization (several times independently) during flowering plant evolution (Winter et al, 2002), probably owing to a selective advantage (Lenser et al, 2009). Autoregulatory circuits of B-class proteins also partially diverged following more recent gene duplication events and differential gene loss (Lee and Irish, 2011), for example in Solanaceae (Rijpkema et al, 2006;Geuten and Irish, 2010) and the basal eudicot opium poppy (Papaver somniferum) (Drea et al, 2007).Changes in homeotic gene expression in the different floral whorls have suggested a role for homeosis in the evolution of flower morphologies (reviewed by Hintz et al, 2006). Heterotopic expression of B-class genes in first whorl floral organs has been implicated in the formation of petaloid tepals instead of sepals in tulips (Kanno et al, 2003), as proposed in the 'shifting boundaries' model (Van Tunen and Angenent, 1993).…”
mentioning
confidence: 99%